ANALISIS STRATEGI PEMASARAN UD. ACC PLASTIK MENGGUNAKAN METODE SWOT DAN AHP GUNA MENINGKATKAN VOLUME PENJUALAN - Wahyu Andhika Ivan S; Mochammad Singgih (LPPM Universitas Bina Bangsa, 2023)
UD. ACC Plastics Surabaya is a company engaged in the household furniture plastic industry business. In terms of the company's sales in 2022 it still has not reached the target, so the company must have a solution to this problem so that its sales volume can increase and reach sales targets. UD ACC Plastics through the SWOT method produced an IFE Matrix with a total score of 0.7098 while an EFE Matrix with a total score of 0.3512. The priority strategy AHP method that can be implemented in the Company is the SO Strategy Approaching the nearest market and using technology and information through website marketing to promote products. The WO strategy is to improve product quality by maximizing human resources in order to take advantage of existing technological advances. ST's strategy is to innovate products to survive in the midst of the emergence of similar products by seeking competitive suppliers in order to obtain good raw materials in terms of quality and quantity. WT's strategy is to cooperate with nearby markets to expand the business network by setting prices. The marketing strategy implemented at UD ACC Plastics is to approach the nearest market to establish cooperation in the sales sector, use technology and information through website marketing to promote products, improve product quality, maximize human resources, innovate so that products survive amidst emergence of similar products, looking for competitive suppliers in order to get good raw materials in terms of quality and quantity, setting prices that can compete with other businesses